2013
DOI: 10.1111/j.1542-2011.2012.00242.x
|View full text |Cite
|
Sign up to set email alerts
|

Expanded Care for Women and Families after Preterm Birth

Abstract: Prematurity is a complication of pregnancy for 1 in 8 families in the United States. The focus of care after preterm birth shifts to the fragile newborn, while the needs of the woman and her family may be overlooked. There are many challenges for parents, including impaired parent-newborn attachment, difficulties with breastfeeding, postpartum mental health, and family disruption. Premature birth may even risk the developing relationship between parents and their child. Comprehensive care is recommended for pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 66 publications
(113 reference statements)
1
10
0
5
Order By: Relevance
“…The nursing team taking care of hospitalized infants has been considered a mediator that may facilitate or interfere in the development of the mother-child relationship [6, 13], responsible for carrying out actions aimed at providing practical care [9, 13]; however, there are often difficulties in promoting actions to improve mother-child bonding [14]. With respect to this difficulty, the results of this study showed the nursing staff took certain actions to facilitate the mother-child relationship such as encouraging contact between the mother and her baby, supporting different ways of bringing her closer to the infant, and promoting informal conversations that allowed the mothers to talk about their difficulties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nursing team taking care of hospitalized infants has been considered a mediator that may facilitate or interfere in the development of the mother-child relationship [6, 13], responsible for carrying out actions aimed at providing practical care [9, 13]; however, there are often difficulties in promoting actions to improve mother-child bonding [14]. With respect to this difficulty, the results of this study showed the nursing staff took certain actions to facilitate the mother-child relationship such as encouraging contact between the mother and her baby, supporting different ways of bringing her closer to the infant, and promoting informal conversations that allowed the mothers to talk about their difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…Women often feel incapable of caring for, or protecting her baby, and this feeling interferes with the way they interact with the newborn and the development of the mother-child relationship [4, 5]. The support of HCPs may help mothers of premature babies to deal with the difficulties associated with this situation, to seek and establish closeness and bonds of attachment with their babies [68]. …”
Section: Introductionmentioning
confidence: 99%
“…A prematuridade também tem grande impacto no desenvolvimento do vínculo mãebebê, no aleitamento materno (AM), na saúde mental materna e em toda a família (KANTROWITZ-GORDON, 2013). Assim, deve-se considerar o custo emocional com sofrimento e estresse decorrente do luto antecipado pela perda do bebê idealizado, a necessidade de cuidados de alta complexidade com internação prolongada de muitos prematuros e a separação da família.…”
Section: A Prematuridade No Contexto Da Saúde Públicaunclassified
“…Sabe-se que, mesmo com o apoio e orientações disponíveis nas unidades neonatais, a ordenha de leite é uma experiência difícil para muitas mães de RN pré-termo e de muito baixo peso que estão hospitalizados e não podem ser amamentados (ACUNÃ-MUGA et al, 2014). A expressão do leite é desconfortável, o bombeamento das mamas pode levar ao trauma mamilar, além dos desafios logísticos no armazenamento e transporte do leite ordenhado (KANTROWITZ-GORDON, 2013). Para garantir a produção de leite em mães de prematuros recomenda-se que as primeiras expressões de leite aconteçam o mais precocemente possível e mantenha pelo menos seis expressões por dia (ACUNÃ-MUGA et al, 2014).…”
Section: As Dificuldades Do Ame Para Os Prematuros E Suas Mãesunclassified
See 1 more Smart Citation